FINANCING DEPOSIT RATIO, BADAN OPERASIONAL PENDAPATAN OPERASIONAL, NON PERFORMING FINANCING DAN PROFITABILITAS PERUSAHAAN PERBANKAN SYARIAH DI INDONESIA - Dodik Hartanto; Siti Nurlaela; Kartika Hendra Titisari (Universitas Bandar Lampung (UBL), 2020)
This study aims to determine, test and analyze the FDR, BOPO, NPF and Profitability of sharia banking companies in Indonesia which are registered in the Financial Services Authority (OJK) fourth quarter financial statements of sharia banking companies in the 2016-2018 period. This research is a quantitative research. The population in this study is Islamic banking companies registered with the Financial Services Authority (OJK). The sample in this study was taken using a purposive sampling method that met the sample criteria desired by the researcher. The data used in this study is in the form of documentation. Data analysis techniques used in this study are multiple linear regression analysis and classic assumption test. Based on these results what is done shows that Financing Deposit to Ratio, Operational Costs Operating Income, and Non Performing Financing affect the profitability of Islamic banking companies.